Novel Dermal Delivery Cargos of Clobetasol Propionate: An Update - Anroop B. Nair; Sunil Kumar; Pooja Dalal; Chahat Nagpal; Sweta Dalal; Rekha Rao; Nagaraja Sreeharsha; Shery Jacob (MDPI AG, 2022)
Dermal disorders such as psoriasis and eczema are associated with modifications in the chemical and molecular composition of the skin. Clobetasol propionate (CP), a superpotent topical glucocorticoid, is widely used for the therapeutic management of various skin conditions, owing to its strong anti-inflammatory, antipruritic, vasoconstrictive, and antiproliferative activities. Safety studies demonstrated that CP is safer for a shorter period, however, with prolonged application, it shows secondary side effects such as photosensitivity, Cushing-like syndrome, allergic contact dermatitis, osteonecrosis, hypopigmentation, steroid acne, and skin atrophy. Therefore, the US FDA (United States Food and Drug Administration) has restricted the usage of CP to not more than 15 days. Research scientists addressed its several formulations and drug delivery issues, such as low water solubility, less stability, photodegradation, and poor absorption, by incorporating them into novel nanobased delivery platforms. With the utilization of these technologies, these drawbacks of CP have been resolved to a large extent to reestablish this moiety. This article explores the physicochemical properties and mechanism of action of CP. Additionally, an attempt has been made to discover and highlight the possible features of the novel nanosystems, including nanoemulsions, nanosponges, solid lipid nanoparticles, nanostructured lipid carriers, and nanogels, reported for CP. The stability and safety concerns of CP, along with its commercial status, are also discussed.